BEYOND LIKES AND FOLLOWS: HOW AL INFLUENCERS DRIVE REAL SALES FOR INDONESIAN MSMEs (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) is a very important industry in Indonesia. MSMEs support large-scale businesses and they are crucial to job creation, poverty alleviation, growth, and social inclusion. The purpose of this study is to determine the influence of ai influencers on digital marketing content and ultimately affect the sales of Indonesian MSMEs. This research uses theoretical literature review as a research method. Authors found that AI influencers affect digital marketing contents, and digital marketing contents affect sales of Indonesian MSMEs. Indonesian MSMEs should use AI influencers to promote their products or services.
Keywords: Indonesia; MSMEs; sales; AI; influencer